THE INFLUENCE FACTORS OF TRAINING MOTIVATION, PEER SUPPORT AND SUPERVISORY SUPPORT THAT AFFECT TRANSFER OF TRAINING: A CASE OF INTI COLLEGE, SARAWAK - Jason wong, Tee Hock (Universiti malaysia sarawak (UNIMAS), 2009)
tlbe results from studying and examining the predictor of transfer of training from an instructional to a organization environment are presented. Previous and prior research has indicated that transfer of training is a result from organizational contextual (peer support and supervisory support). Organizational contextual (peer support and supervisory support) was introduced as a proximal training outcome and further connected to the distal training outcome, transfer of training (TOT). Analysis with questionnaires revealed that organizational contextual factor such as supervisory support was related to transfer of training. Furthermore, past and present literatures were introduced to further support the nature of the proposed model. Descriptive statistic, correlation analysis and regression analysis were used to analyze the data. The descriptive data about the background of respondent were also discussed. Secondly, the Stepwise regression analysis was carried out and showed that both supervisory support and peer support mediates the relationship between training motivation and transfer of training. Thirdly, a standard regression concluded that training motivation had a non significant relationship with transfer of training, P=.239 at a significant level of .05. In conclusion, the results showed that both peer support and supervisory support plays an important mediating role of the relationship between training motivation and transfer of training,. Some suggestion was proposed for the organization and researchers to help nurture the preparation for high quality and competent HR managers. Based on this study, it would lead to the enhancement of trainees' skill and knowledge transfer in private organization.